2023
DOI: 10.1021/acscatal.2c05144
|View full text |Cite
|
Sign up to set email alerts
|

Modulating O–H Activation of Methanol Oxidation on Nickel-Organic Frameworks for Overall CO2 Electrolysis

Abstract: Advanced anodic electrocatalysis is essential for boosting overall carbon dioxide (CO2) electrolysis. In this work, we demonstrate partially pyrolyzed nickel-organic frameworks for efficient methanol oxidation at the anode. Experimental validation and theoretical calculation results demonstrate that the partial deligandation could maintain the porous skeleton and ensure more accessible nickel sites for in situ transformation to the Ni-OOH active phase, modulating the O–H activation pathway of methanol upgradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…[154][155][156] Fundamental research has predicted that crystalline faces play a pivotal role in the deep reduction of CO 2 . These hypotheses were systematically elucidated by single-crystal studies as a simplified picture, and the well-defined Cu (100) single-crystal surface showed higher C 2+ selectivity than its (111) and (110) counterparts due to the preferred *CO dimerization pathway (Figure 3b). [157] Gong et al developed a dynamic depositionetch-bombardment method to prepare Cu (100)-rich films.…”
Section: Electronic Structurementioning
confidence: 99%
“…[154][155][156] Fundamental research has predicted that crystalline faces play a pivotal role in the deep reduction of CO 2 . These hypotheses were systematically elucidated by single-crystal studies as a simplified picture, and the well-defined Cu (100) single-crystal surface showed higher C 2+ selectivity than its (111) and (110) counterparts due to the preferred *CO dimerization pathway (Figure 3b). [157] Gong et al developed a dynamic depositionetch-bombardment method to prepare Cu (100)-rich films.…”
Section: Electronic Structurementioning
confidence: 99%
“…The NiFe-PBA catalyst shows a high catalytic performance in terms of activity (500 mA cm −2 ) and faradaic efficiency (95.8%) toward formate. 9,29,30,36–44 Compared with the catalysts reported, NiFe-PBA/NF can achieve the highest current density while maintaining the FEs of formic acid close to 100%.…”
Section: Resultsmentioning
confidence: 96%
“…21 Xia and co-workers proposed that the high-valence Ni-OOH phase is the active phase for EMU, which can be in situ generated and accumulated during the anodization of a partially pyrolyzed Ni terephthalate MOF. 22 Fu's group proposed that the in situ -formed Ni-OOH phase collaborated with the SeO x species simultaneously generated during the pre-oxidation of NiSe as the dominant species that govern EMU behavior. 15 In addition, Xu's group revealed that the in situ -formed Cu 2+ species on the surface of Cu 3 N could act as active sites for methanol electro-oxidation, which is the key active phase for the formation of formate.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a series of transition-metal-based catalyst compounds have been explored for EMU, and current studies indicate that high-valence transition metal ions could serve as catalytically active sites for methanol-to-formate conversion. 5,15,[17][18][19][20][21][22] Hence, enriching local high-valence species or promoting the in situ generation of such active sites via an electrochemical pre-oxidation process could effectively improve EMU behavior. For example, Peng and colleagues fabricated an Fe 2 O 3 /NiO heterojunction catalyst, which could lead to the stabilization of high-valence Ni 3+ ions as active sites for EMU and further realize enhanced catalytic activity via beneficial Ni-O-Fe interfaces.…”
Section: Introductionmentioning
confidence: 99%